92 Balint Groups: An Initiative to Help Residents Better Understand the Clinician-Patient Relationship. (29th October 2021) - Finstad, Warner; Jeong, Dayae; Humphreys, Joanna; Lord, Sarah; Diskin, Catherine; Lam, Justin
Abstract: Primary Subject area: Medical Education Background: A Balint group is an educational tool that allows residents to reflect on challenging experiences with the doctor-patient relationship. Guided by trained facilitators, residents consider these cases from the doctor, patient and doctor-patient perspectives together with their colleagues. Balint groups can support the recognition of the emotional complexity underlying these interactions, which in turn reduces burnout, improves patient care and team dynamics, and strengthens professional identities. Objectives: 1) To evaluate the effect of Balint groups on trainees' perceived comfort levels in navigating, debriefing, and supporting peers through challenging patient-physician encounters; 2) To evaluate the effect of Balint groups on the perceived culture of support within the paediatric residency program at the University of Toronto. Design/Methods: The University of Toronto Pediatrics Residency Program incorporated Balint groups into the curriculum in 2018. Supported by faculty, residents led their introduction and improvement using Quality Improvement methodology. Outcome measures included perceived comfort levels in navigating and supporting peers through challenging patient-physician encounters, and the perceived culture of support within the program. Outcome measures were obtained using a 5-point Likert scale. Rates of group participation were collected as a process measure. Results: All outcome measures improved between the first and second year of Balint group implementation. Residents' comfort levels in navigating difficult patient-physician encounters increased from a mean of 2.5 (out of a 5-point Likert scale) to 3.0, in debriefing complex scenarios from 3.1 to 3.9, and in supporting peers from 3.2 to 3.8. The perceived culture of peer support improved from a mean of 3.5 to 4.2. Conclusion: A Balint group is a reflective educational tool, which has a positive impact on residents' experiences navigating patient relationships. Introducing these sessions at our institution has shown an encouraging trend in improving residents' comfort levels with difficult clinical encounters and fostering a culture of support.